INVESTIGATING THE CORRELATION BETWEEN STUDENTS’ GRAMMAR MASTERY AND READING COMPREHENSION ACHIEVEMENT - Eka Septiani; Chuzaimah D Diem; Muhammad Yunus (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2018)
Abstract: The objectives of the study were to find out whether or not there were a significant correlation between students’ grammar mastery and reading comprehension achievement and a significant contribution of the students’ grammar mastery to their reading comprehension achievement. There were 120 eighth graders of one junior high school got involved as participants of this study. The data were collected by using grammar and reading comprehension tests and analyzed statistically by applying Pearson product moment correlation analysis and linear regression. The findings showed that there was a strong positive correlation between the students’ grammar mastery and their reading comprehension in which r-obtained (0.739) was higher than r-table (0.1793). The regression analysis also showed that there was significant contribution of the students’ grammar mastery (54.7%) to their reading comprehension achievement.Keywords: grammar mastery, reading comprehension, eighth graders